DAMPAK INSENTIF PPH PASAL 21 SAAT PANDEMI COVID19 TERHADAP TAKE HOME PAY DAN PELAPORAN SPT TAHUNAN - Bayu Sarjono (Jurnal Bisnis Terapan, 2021)
The purpose of this study is to determine the impact of incentives Income Tax Article 21 for the withholding and reporting of the Annual income Tax a Permanent Employee. This type of research is descriptive research with case study approach of research about the status of subject of the study with respect to a specific phase or typical of the whole personality. The data were obtained from dokumetansi i.e. data earnings a permanent employee, the calculation of Income Tax Article 21, and form 1721 A1. The Unit of analysis in this research was the individual as a lecturer at the University of Y included in the KLU taxpayers affected by the pandemic Covid19.Income tax Article 21 for the Period of January to March to dependents of employees, thereby reducing the magnitude of the Take Home Pay received. From April to December, employees with certain criteria were given an incentive of income Tax Article 21 by the Government and income Tax withheld by the employer was given simultaneously with the monthly income. With the tax incentives it can increase the Take Home Pay received. Article 21 income tax Borne by the Government received by the employee from the employer is not taken into account as income subject to taxation. Therefore, it must be reported in the tax return (SPT) Annual Personal Income Tax. But in this case the employer does not provide data to the employee about the amount of income Tax Article 21 Borne by the Government.